A Sequential Study on the Pathology of Peste Des Petits Ruminants and Tissue Distribution of the Virus Following Experimental Infection of Black Bengal Goats - Begum, Shahana; Nooruzzaman, Mohammed; Islam, Mohammad Rafiqul; Chowdhury, Emdadul Haque (Frontiers in Veterinary Science, 2021)
We studied the sequential pathology of peste des petits ruminants (PPR) in Black Bengal goats and analyzed virus distribution in tissues and virus shedding following experimental infection with a Bangladeshi isolate of lineage IV PPR virus (PPRV). The early clinical signs like fever, depression, and ocular and nasal discharges first appeared at 4 to 7 days post-infection (dpi). Three out of eight inoculated goats died at 13, 15 and 18 dpi, and the rest were killed at different time points from 5 to 18 dpi. Initially, the virus multiplied mostly in the lymphoid organs of the pharyngeal region and caused extensive lymphoid destruction and hemorrhages. This was followed by viremia, massive virus replication in the lungs, and pneumonia along with the appearance of the clinical signs. Subsequently, the virus spread to other organs causing necrotic and hemorrhagic lesions, as well as the virus localized in the upper respiratory, oral and intestinal mucosa resulting in catarrhal, erosive, and ulcerative lesions. On hematological and biochemical investigation progressive leukopenia and hypoproteinemia, a gradual increase of serum metabolites and enzymes associated with liver and kidney damage, and electrolyte imbalance were observed. Seroconversion started at 7 dpi and all the surviving animals had serum antibodies at 14 dpi. Virus shedding was observed in nasal and ocular secretions at 4 dpi and in feces and urine at 14 dpi, which gradually increased and continued till the end of the experiment (18 dpi) despite seroconversion. Therefore, the virus shedding of naturally infected seroconverted goats should be monitored for effective control strategies.